2006
DOI: 10.1002/ana.21033
|View full text |Cite
|
Sign up to set email alerts
|

Neural precursors attenuate autoimmune encephalomyelitis by peripheral immunosuppression

Abstract: IV administration of neural precursors inhibits EAE by a peripheral immunosuppressive effect. Our findings suggest a profound bystander inhibitory effect of NPCs on T-cell activation and proliferation in the lymph nodes, leading to amelioration of EAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
256
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 236 publications
(271 citation statements)
references
References 37 publications
12
256
1
2
Order By: Relevance
“…Peripheral immune modulation has also been observed following systemic MSC and NPC transplantation in EAE, owing to a remarkable accumulation of transplanted cells at the level of secondary lymphoid organs, where T-cell proliferation and production of proinflammatory cytokines were inhibited (Einstein et al, 2007;Pluchino et al, 2009b;Zappia et al, 2005). Furthermore, exclusive targeting of the peripheral immune system has been reported in relapsing EAE in mice after subcutaneous NPC injection (Pluchino et al, 2009b).…”
Section: Signaling At a Distance (Endocrine)mentioning
confidence: 99%
“…Peripheral immune modulation has also been observed following systemic MSC and NPC transplantation in EAE, owing to a remarkable accumulation of transplanted cells at the level of secondary lymphoid organs, where T-cell proliferation and production of proinflammatory cytokines were inhibited (Einstein et al, 2007;Pluchino et al, 2009b;Zappia et al, 2005). Furthermore, exclusive targeting of the peripheral immune system has been reported in relapsing EAE in mice after subcutaneous NPC injection (Pluchino et al, 2009b).…”
Section: Signaling At a Distance (Endocrine)mentioning
confidence: 99%
“…Following systemic delivery, immune regulation by NPCs occurs in secondary lymphoid organs, such as the lymph nodes [177] or the spleen [178].…”
Section: Immune Modulationmentioning
confidence: 99%
“…One school of thought was suggested that NPCs induce apoptosis of Th1 cells, but not Th2 cells, selectively, via the inflammationdriven up-regulation of membrane expression of functional death receptor ligands (e.g., Fas Ligand, TNF-related apoptosis-inducing ligand-TRAIL, Apo3 ligand) on NPCs [173]. Alternatively, it has been suggested that NPCs inhibit T-cell activation and proliferation by a nonspecific, bystander immune suppressive action [177]. This notion emerged from co-culture experiments that showed a striking inhibition of the activation and proliferation of EAE-derived, as well as naive, T cells by NPCs, following stimulation by various stimuli [171,177,179].…”
Section: Immune Modulationmentioning
confidence: 99%
See 2 more Smart Citations